Automated strabismus evaluation: a critical review and meta-analysis - Hartness, Emma M.; Jiang, Fangfang; Zamba, Gideon K. D.; Allen, Caroline; Bragg, Tara L.; Nellis, Julie; Dumitrescu, Alina V.; Kardon, Randy H. (Frontiers in Neurology, 2025)
IntroductionAdult strabismus has a wide range of etiologies and necessitates clinical evaluation for appropriate treatment. Advancements in eye tracking technology show promise for the development of clinically accurate, automated evaluation and diagnosis of peripheral and central causes of ocular misalignment. However, multiple barriers prevent the incorporation of automated devices into clinical use. This study aimed to perform a quantitative meta-analysis and qualitative assessment of published reports of devices capable of automated strabismus evaluation.MethodsA systematic search of the literature was conducted to identify reports of automated strabismus evaluation published between the years 1949–2025. Sixty-nine studies were identified through the literature search, and 17 of these studies qualified for statistical meta-analysis of automated device quality compared to gold standard clinical evaluation. We also analyzed factors affecting clinical use, including device portability, cost, and applicability toward patients with extreme angles of strabismus or anatomic variances, among others.ResultsMeta-analysis demonstrated a pooled estimation of correlation of 0.87 [95% CI: (0.81, 0.91)] between results obtained by devices capable of automated strabismus evaluation in the literature and gold standard clinical evaluation. We identified advantages and limitations of previous models and offered guidelines to facilitate the advancement of device capabilities toward the level of gold standard expert clinical evaluation, and to facilitate the clinical implementation of these devices.DiscussionWhile barriers exist between experimental testing and clinical incorporation, automated strabismus technology shows promise for rapid, precise, and accurate evaluation of strabismus and has the potential to expand access to ophthalmic care in cases of low-resource or remote areas that lack local expert clinical personnel.